Analisis Kandungan Mikroplastik pada Air Payau Teluk Kendari (Studi Kasus Muara Sungai Wanggu) - Dewi, Wa Ode Nanang Trisna; Erif, La Ode Muhammad; Garusu, Ema Hermawati; Jamal, Fahrezi; Azmi, Aulia Ulil (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the content of microplastics in brackish water in Kendari Bay by taking two strategic points, namely the mouth of the Wanggu River as the main entrance to materials from the mainland, and the mouth of Kendari Bay as the outlet of water into the open sea. The method used in this study is quantitative descriptive with a purposive sampling method for the determination of location and sampling points, which includes water and sediment sampling. Microplastic separation using filtration techniques, and morphological identification with stereoscopic microscopy. The data were analyzed to determine the amount, size, shape, and color of microplastic particles per milliliter of water. The results showed that the microplastic form in brackish water and sediment consists of fibers, films, fragments, and foam. The colors of the microplastics found were generally seen at both observation stations (locations), namely black (37%), transparent (31%), yellow (13%), green (13%), and blue (6%). The size of microplastics at the overall sampling point, both in brackish water and in sediments with fiber shapes ranging from approximately 0.1 mm-0.2 mm, film shapes were found with sizes ranging from 0.02 mm-0.06 mm. The fragment shape ranges in size from 0.04 mm-0.06 mm and the foam shape in size ranges from 0.01 mm to 0.27 mm. The results of microplastic measurements in two locations, namely the first location of the Wanggu River estuary obtained an abundance of microplastics in brackish water samples calculated on a scale of 150 mL, showing that microplastics at the sampling point of mangrove areas had the highest concentration, namely 16,080 particles/150 mL, followed by estuaries (13,320 particles/150 mL), and residential areas (10,560 particles/150 mL). The total abundance of all locations reached 39,960 particles/150 mL, with foam being the most abundant type (16,560 particles/150 mL), followed by fragment form (9,000 particles/150 mL), fiber (8,850 particles/150 mL), and finally film (5,550 particles/150 mL). From the relative abundance, it shows that in general, the most relative abundance is in the form of foam microplastics, both in estuaries (42.1%), residential areas (47.2%), and mangroves (37.13%). The total abundance of microplastics in the sediment of the Wanggu River Estuary is 23,860 particles/100 grams of sediment or 238.6 particles/gr. These findings indicate a fairly high level of microplastic contamination, especially in areas adjacent to residential and terrestrial activities.